Enrichment of a mixed microbial culture of PHA-storing microorganisms by using fermented hardwood spent sulfite liquor - Pereira, Joana (2021)
Pulp and paper factories produce several residues that can be explored and valorized through polyhydroxyalkanoate (PHA) production via a three-step process. The objective of this work was focused on the selection step. Acidified hardwood spent sulfite liquor (HSSL), a fermented waste stream from a pulp and paper factory, was used to select a mixed microbial culture (MMC) in a sequencing batch reactor (SBR) operated for 156 days under different operational conditions. The MMC adapted to the imposed conditions, revealing its robustness whenever the operational parameters were changed. Feast-to-Famine ratio was kept below or equal to 0.2, with constant production of a copolymer of P(3HB-co-3 HV), and with storage contents values over 30 %. Changes in the operational conditions, namely cycle length, and organic load rate (OLR), successfully led to the selection of an MMC with a stable accumulation capacity and an increased biomass concentration. Next Generation Sequencing analysis was performed on samples collected during the SBR operational period. The analysis of the microbial composition of the MMC showed a rise in PHA-accumulating bacteria over time. Acidovorax and Comamonas species were found mainly to drive the PHA storage process during the first two periods of operation. After an increase in the OLR, in the last period, a shift towards Comamonas dominance occurred, suggesting a higher tolerance to the inhibitory compounds of the HSSL for this genus.